GreenCycle: Ubah Limbah Dapur Jadi Pupuk Organik Cair di Desa Tegalweru - Muhammad Rifa'i; Muhammad Rakha Mahaputra; Marcelina Kusumaningtyas Ari Widyastuti; Bintang Alif Ramadhan; Yuliada Pawestri; Shintya Dita Afrina; Frannanda Raydhika Lyfanni; Janu Narendra; Angelica Wijaya; Febrianto Anung Anindito (Jurnal Riset Multidisiplin Edukasi, 2026)
Household waste, particularly organic kitchen waste, frequently poses environmental challenges if not managed properly, as observed in Tegalweru Village. The "GreenCycle" program aims to provide practical education and skills to PKK (Family Welfare Movement) members in transforming kitchen waste into Liquid Organic Fertilizer (LOF). The methodology employed includes theoretical socialization, practical demonstrations of LOF production using simple composters, and a two-week fermentation monitoring period. The results indicate a significant increase in community understanding regarding waste segregation and organic fermentation techniques. The positive impact includes a reduction in the volume of waste disposed of into the environment and the creation of self-sufficient fertilizer for residents' home gardens. This program is expected to continue independently to support family food security and village environmental sustainability.